Using Biochar to Improve Soil Fertility and Productivity of Drought-Tolerant Sweet Potatoes in Thanh Hoa Coastal Sandy Soil - Sy Chung, Le; Quoc Viet, Nguyen; Minh Tien, Tran; Minh Phuong, Nguyen; Sy Chinh, Le; Anh Hung, Pham (VNU Journal of Science: Earth and Environmental Sciences, 2024)
The coastal area of Thanh Hoa province has a large proportion of sandy soil and is suffering negative impacts from climate change that affect crop productivity. The aim of this study is to investigate the use of biochar to improve the soil fertility and productivity of drought-tolerant sweet potatoes. The effect of biochar contents on the productivity of three sweet potatoes VC 04-24, KL C3, and VC 68-2 in the coastal sandy soil area of Thanh Hoa province was examined. The results indicated that the yield of sweet potatoes was the highest when applying five tons of biochar per hectare, equivalent to using 10 tons of manure. With the same biochar content, the productivity and other factors related to the product quality of these sweet potatoes such as the number of tubers per plant and the average mass of tuber were the highest. In detail, the estimated commercial productivity of VC 04-24, KL C3, and VC 68-2 were 25.46, 24.92, and 21.76 ton/ha, respectively. With the least significant difference at the probability of 0.05% (LSD 0.05 ), the VC 04-24 and KL C3 showed high productivity. The economic efficiency of the sweet potatoes-growing model at Hai An commune, Tinh Gia district, Thanh Hoa province showed that the productivity of the model was 24 tons/ha, higher than the actual productivity of the control model (20.2 ton/ha). The productivity and the economic efficiency of the model were 18.8% and 31.38% higher than those of the control model, respectively. In addition, the test results showed that using 5-6 ton/hectare of biochar can improve the physical and chemical properties of soils.